ANALYSIS OF THE COMPETITIVENESS OF TOBACCO INDONESIA IN THE INTERNATIONAL MARKET - Putra, Handy Tribawana; Muhaimin, Abdul Wahib; Suhartini, Suhartini (HABITAT, 2015)
Tobacco is one of main export commodity from the plantation sub-sector of Indonesia. Indonesian tobacco exports in recent years,Â  2008 to 2014 experienced an increase or had a positive trend. It shows that the tobacco has the potential to be developed. Competitiveness analysis using the calculation of Revealed Comparative Advantage (RCA), while the analysis of competitivness Export Index (ECI) to see the trend of competitiveness. If Indonesia had RCA more than one, so Indonesia has a competitive advantageÂ  and if Indonesia has a value of ECI more than one, then Indonesia is said to have a good competitiveness development. Based on the analysis of tobacco RCA Indonesia in the international market, Indonesia has a comparative advantage compared to competing countries of Indonesia, such as France and Thailand with RCA> 1. Because Indonesia has a high export value for the tobacco and abundant natural resources as well as the amount of labor that much.The results of the analysis of ECI, to determine the trend of the competitiveness of Indonesian tobacco than the comparison countries, namely France and Thailand, shows Indonesian tend to have better competitiveness development value ECI> 1. This is because of Indonesia has a better advantage export than France and Thailand. Based on the analysis of RCA and ECI, it can be concluded that in the future, tobacco will be a interested commodity because of the increased demand, it will make Indonesia must have a competitiveness in domestic and international markets.